Golf skill: The effective acquisition and application of biomechanics - Farrow, D. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
Contemporary applied golf practice is littered with instructional advice and products purported to improve the biomechanics, and ultimately performance of the golf swing. In this presentation I will apply skill learning theory to assess the relative efficacy of the common approaches claimed to facilitate golf skill as they relate to instruction, feedback and guidance devices.